Vaginal Seeding of Babies Born via Cesarean. Issue 1 (January 2018) - Simpson, Kathleen Rice
Abstract : With growing interest in the microbiome and its implications for health, more research is evolving on how interventions during labor and birth influence newborn and infant microbiota. Some parents are requesting vaginal seeding of their babies born via cesarean. Possible benefits are theoretical and research to date is quite limited, however, there are significant potential risks of unintended harm if infection is transferred to the baby with this procedure. A brief summary of vaginal seeding is offered with recommendations for practice.